Maternal exposure to zinc oxide nanoparticles causes cochlear dysfunction in the offspring - Campagnolo, Luisa; Lacconi, Valentina; Bernardini, Roberta; Viziano, Andrea; Pietroiusti, Antonio; Ippoliti, Lorenzo; Moleti, Arturo; Sisto, Renata (Frontiers in Toxicology, 2024)
Introduction: Zinc oxide nanoparticles (ZnO NPs) have been engineered and are largely used in material science and industry. This large and increasing use justifies a careful study about the toxicity of this material for human subjects. The concerns regard also the reproductive toxicity and the fetotoxicity. Materials and methods: The effect of the exposure to ZnO NPs on the cochlear function was studied in a group of pregnant CD1 mice and in their offspring. This study is part of a larger toxicological study about the toxicity of ZnO NPs during pregnancy. Four groups were analyzed and compared, exposed and non-exposed dams and their offspring. The cochlear function was quantitatively assessed by means of Distortion Product Otoacoustic Emissions (DPOAEs). Results and discussion: A large statistically significant difference was found between the non-exposed dams offspring and the exposed dams offspring (p = 1.6 · 10−3), whose DPOAE levels were significantly lower than those of non-exposed dams offspring and comparable to those of the adults. The DPOAE levels of the exposed and non-exposed dams were very low and not significantly different. This occurrence is related to the fact that these mice encounter a rapid aging process. Conclusion: Our findings show that maternal exposure to ZnO NPs does not reflect in overt toxicity on fetal development nor impair offspring birth, however it may damage the nervous tissue of the inner ear in the offspring. Other studies should confirm this result and identify the mechanisms through which ZnO NPs may affect ear development.